2011
DOI: 10.1007/s10767-011-9113-0
|View full text |Cite
|
Sign up to set email alerts
|

School History Textbooks and Historical Memories in Japan: A Study of Reception

Abstract: Memory wars in Asia still revolve around Japan. Much has been discussed on the so-called kyōkasho mondai (history textbook controversies), yet, not much has been explored on the domestic social function of history textbooks per se. Emphasizing creators of history narratives (and their production), the field tends to overlook the audience, or, receivers in the process. In this article, by referring to the original interviews with Japanese college students, I question the very assumption of the creator-receiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Currently, in well -developed countries, we can observe that public education is becoming less influential. Nevertheless, various case studies show that it can still serve as an effective instrument in the government's remembrance policy: it is used to establish emotional relationships between citizens and the interpretation of the past (Dror 2001); to promote a selection of events which are significant for national identity (Yablonka 2009); to associate past experiences with preferred behaviours (Meseth -Proske 2010); to shape political preferences (Bukh 2008;Fukuoka 2011) and even to mobilise young citizens and involve them as an additional force in ongoing political conflicts (Wang 2008). 4 The organisation of time results in an official calendar of political holidays and it informs citizens about the past events which are to be commemorated or celebrated.…”
Section: Figure 1: Relationships and Interdependencies Among Instrumementioning
confidence: 99%
“…Currently, in well -developed countries, we can observe that public education is becoming less influential. Nevertheless, various case studies show that it can still serve as an effective instrument in the government's remembrance policy: it is used to establish emotional relationships between citizens and the interpretation of the past (Dror 2001); to promote a selection of events which are significant for national identity (Yablonka 2009); to associate past experiences with preferred behaviours (Meseth -Proske 2010); to shape political preferences (Bukh 2008;Fukuoka 2011) and even to mobilise young citizens and involve them as an additional force in ongoing political conflicts (Wang 2008). 4 The organisation of time results in an official calendar of political holidays and it informs citizens about the past events which are to be commemorated or celebrated.…”
Section: Figure 1: Relationships and Interdependencies Among Instrumementioning
confidence: 99%
“…Th erefore, remembrance narratives may mediate proliferation of civic attitudes, values and behaviours, causing some limitation to further democratic development (Komalasari, Saripudin, 2017;Hailat, 2017). Th ey produce boundaries for public debates, defi ning which actions are either historically appropriate or against the nation's tradition or interests (Fukuoka, 2011). Finally, the public education system can serve as a medium for propaganda and manipulation of public opinion -promoted interpretations of the past may legitimise social, economic or political order and refocus citizens from the current state of the nation to unresolved past injustices (Wang, 2008).…”
Section: Joanna Marszałek-kawa Patryk Wawrzyńskimentioning
confidence: 99%
“…Indeed, Schuman et al note that revisionists' beliefs reached only the people already open to such re-evaluations. Finally, in the recent research on reception of history textbooks in Japan, Fukuoka (2011) has shown that students evaluated -and sometimes dismissed -textbooks' narratives in light of other socio-political circumstances and alternative sources of memory.…”
Section: Individual Beliefs On the Past And Reception Of Collective Mmentioning
confidence: 99%